Diatomáceas em corpos d'água da região noroeste do Estado do Ceará : Mediophyceae, Coscinodiscophyceae e Bacillariophyceae (Eunotiales e Cymbellales) - Maciel, Maria Gabrielle Rodrigues, 1995- (2021)
Orientadora: Profa. Dra. Thelma Alvim Veiga Ludwig